Conversational Analysis on Politeness in Online Class Discussions: Exploring Turn-Taking and Relational Work Strategies Between Lecturer and Students - Yatni Fatwa Mulyati; Didin Nuruddin Hidayat; Nida Husna; Alek Alek; Shirley Baker (IAIN MADURA, 2023)
In the teaching-learning process, the lecturers usually play the role of dominant turn-takers. Meanwhile, students mostly perform as small turn-takers. In EFL classrooms, different turn-taking patterns are essential to analyze to identify the students' language politeness during the turn-taking process. The present study analyzed the turn-taking and relational work concerning politeness in online class discussions. For this study, a conversational analysis was performed on online class(es) discussions between students and lectures. A video recording of a classroom conversation between ELT and TEFL was employed. The study found that 16 out of 40 quotations displayed a turn-taking of the Appealing Strategy (AS). The relational work strategy of Being Cooperative (BC) was cited in 22 of 40 quotes. In relational work strategies, BC indicated that the students' responses related to what the lecturer mentioned. Turn-taking and relational work strategies could be one of the tools to determine the students' politeness by combining the characteristics as politeness indicators that focus on students' answers when speaking with the lecturer. Further investigations on gender disparities that use turn-taking and relational work to maintain politeness in online lecturer-student dialogues may prove insightful.